FEASIBILITY OF UTILIZATION EAFD AS CEMENT REPLACEMENT IN CONVENTIONAL CONCRETE - Amir Fauzi; Syukri Syukri; Mulizar Mulizar; Muhammad Reza (Politeknik Negeri Lhokseumawe, 2017)
Abstract — Industrial waste products can be considered as renewable resources, one of them is a steel manufacturing, which produced dust waste contain sponge iron, scrap metal and other steel wastes that impacted to environment. This waste material was called Electric Arc Furnace Dust (EAFD). This study investigates the feasibility of using EAFD as a cement replacement compared to silica fume (SF) and fly ash (FA) in terms of Chemical composition, workability, setting time, compressive strength and rapid chloride permeability resistance. The results showed that workability of EAFD is almost similar to control even if percentage of EAFD was increased. It is not refer to FA more workable or SF less workable with increase percentage of replacement. Furthermore, the EAFD significantly affect the setting time, which 3% EAFD replacement bring to prolong final setting time to more than 24 hours, while the setting time of SF and FA did not significant affected along with the increase replacement percentage. In addition, the 3% EAFD is optimum replacement for compressive strength and it is equivalent replacement level to 5% SF and 15% FA. Finally, the EAFD enhance the resistance for rapid chloride permeability more than FA but less than SF.